Analysis of the Influence of Service Innova-Tion Aspects, Rates, With the Mediation of Trust Level on Inter-City Inter-Province Bus Ticket Purchase Retention (Case Study of PO Sinar Jaya) - Eko Yulianto; Zaenal Abidin; Djamal Subastian; Devi Marlita; Yana Tatiana (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the impact of service innovation, pricing, and trust on ticket purchase retention for intercity and interprovincial (AKAP) buses at PO Sinar Jaya. Despite the increasing number of passengers, ticket purchase retention remains suboptimal, and the load factor is only 50%, far below the ideal standard of 70%. This phenomenon suggests that factors beyond passenger volume, such as service innovation and pricing policies, play a crucial role in influencing customer loyalty. The research employs a descriptive method with a quantitative approach. The study population consists of all PO Sinar Jaya passengers in 2023, totaling 5,635,602 passengers. The sampling technique used is Random Purposive Sam-pling. The sample size is determined using Hair’s (2020) formula, based on the number of research indicators. Data was collected through questionnaires, and analysis was conducted using the Structural Equation Modeling (SEM) method with SmartPLS software. The results indicate that service innovation positively influences trust and ticket purchase retention, whereas pricing does not significantly impact trust but positively affects ticket purchase retention. Additionally, trust plays a crucial role in enhancing purchase retention. The findings highlight the importance of service innovation and competitive pricing strategies in improving customer loyalty at PO Sinar Jaya.